Indonesia’s Seaweed in Global Market - Rochaeni, Siti; Firzatullah, Nuranisa; Humaerah, Armaeni; Sari, Rizki Adi Puspita; Junaidi, (Archives of Business Research, 2022)
Seaweed is one of Indonesia’s superior commodities in the global market. The potential for seaweed production itself can be used to gain a competitive position in the global market. The purpose of this research is to analyse the comparative advantage and competitive advantage of Indonesian seaweed in the international market and analyzed the market structure of seaweed in the international market. Indonesia’s seaweed is in the rising star position marked by China and Spain, which means both countries are the potential market to develop. The falling star position is marked by France, South Korea, Chile, and Vietnam, which are unwanted positions but still available for market share improvement. The last opportunity position is marked by the Philippines and USA, which means that there was declining export activity and affected decreased competitiveness. The retreat position is marked in Japan and UK, which is an unwanted market position. The world seaweed market structure is the oligopoly market.